Persistent functional and taxonomic groups dominate an 8,000-year sedimentary sequence from Lake Cadagno, Switzerland - Rodriguez, Paula; Berg, Jasmine S.; Deng, Longhui; Vogel, Hendrik; Okoniewski, Michal; Lever, Mark A.; Magnabosco, Cara (Frontiers in Microbiology, 2025)
Most of our knowledge of deep sedimentary life comes from marine environments; however, despite their relatively small volume, lacustrine sediments constitute one of the largest global carbon sinks and their deep sediments are largely unexplored. Here, we reconstruct the microbial functional and taxonomic composition of an 8,000-year Holocene sedimentary succession from meromictic Lake Cadagno (Switzerland) using shotgun metagenomics and 16S rRNA gene amplicon sequencing. While younger sediments (<1,000 years) are dominated by typical anaerobic surface sedimentary bacterial taxa (Deltaproteobacteria, Acidobacteria, and Firmicutes), older layers with lower organic matter concentrations and reduced terminal electron acceptor availability are dominated by taxa previously identified as “persistent populations” within deep anoxic marine sediments (Candidatus Bathyarchaeia, Chloroflexi, and Atribacteria). Despite these dramatic changes in taxonomic community composition and sediment geochemistry throughout the sediment core, higher-order functional categories and metabolic marker gene abundances remain relatively consistent and indicate a microbial community capable of carbon fixation, fermentation, dissimilatory sulfate reduction and dissimilatory nitrate reduction to ammonium. As the conservation of these metabolic pathways through changes in microbial community compositions helps preserve the metabolic pathway connectivity required for nutrient cycling, we hypothesize that the persistence of these functional groups helps enable the Lake Cadagno sedimentary communities persist amidst changing environmental conditions.